Catalytic Enantioselective Quick Route to Aldol‐Tethered 1, 6‐ and 1, 7‐Enynes from ω‐Unsaturated Aldehydes. Issue 47 (3rd October 2014) - García, Jesús M.; Odriozola, José M.; Razkin, Jesús; Lapuerta, Irati; Odriozola, Amaiur; Urruzuno, Iñaki; Vera, Silvia; Oiarbide, Mikel; Palomo, Claudio
Abstract An effective asymmetric route to functionalized 1, 6‐ and 1, 7‐enynes has been developed based on a direct cross‐aldol reaction between ω‐unsaturated aldehydes and propargylic aldehydes (α, β‐ynals) promoted by combined α, α‐dialkylprolinol ether/Brønsted acid catalysis. This synergistic activation strategy is key to accessing the corresponding aldol adducts with high stereoselectivity, both enantio‐ and diastereoselectivity. The aldol reaction also proceeds well with propargylic ketones (α, β‐ynones) thus enabling a stereocontrolled access to the corresponding tertiary alcohols. The utility of these adducts, which are difficult to prepare through standard methodology, is demonstrated by their transformation into trisubstituted bicyclic enones using standard Pauson–Khand conditions.